Human factors in anaesthetic practice: insights from a task analysis. - Phipps D; Meakin GH; Beatty PC; Nsoedo C; Parker D; Phipps, D; Meakin, G H; Beatty, P C W; Nsoedo, C; Parker, D (BJA: The British Journal of Anaesthesia, 2008)
Background: Despite a growing recognition of the role of human error in anaesthesia, it remains unclear what should be done to mitigate its effects. We addressed this issue by using task analysis to create a systematic description of the behaviours that are involved during anaesthesia, which can be used as a framework for promoting good practice and highlight areas of concern.Methods: The task steps involved in preparing and delivering anaesthesia were identified using hierarchical task analysis (HTA). The systematic human error reduction and prediction approach (SHERPA) was then used to identify potential human errors at each task step and suggest ways of preventing these errors.Results: The number and type of behaviours involved vary according to the 'phase' of anaesthesia, with tasks in the induction room, including induction of anaesthesia itself, being the most demanding. Errors during preoperative planning and perioperative maintenance could be avoided by measures to support information handling and decision-making. Errors during machine checking, induction, and emergence could be reduced by streamlining or automating task steps, or by making changes to the physical design of the work environment.Conclusions: We have demonstrated the value of task analysis in improving anaesthetic practice. Task analysis facilitates the identification of relevant human factors issues and suggests ways in which these issues can be addressed. The output of the task analysis will be of use in focusing future interventions and research in this area.